Czynniki budujące siłę i potęgę państwa na arenie międzynarodowej (Świat Idei i Polityki, 2010)
The concept of power is central to international relations. This article examine the sources of power and the relationship of different power sources. We first begin by review of a taxonomy of power sources, and after that we generate new taxonomy. The starting point for opening the conceptual aperture is to identify the critical dimensions that generate different conceptualizations of power sources. This paper will begin to address these issues and open the door for continued discussion over the nature of power sources in international relations theory and practice.